2017
DOI: 10.1111/dme.13351
|View full text |Cite
|
Sign up to set email alerts
|

Differential increments of basal glucagon‐like‐1 peptide concentration among SLC47A1 rs2289669 genotypes were associated with inter‐individual variability in glycaemic response to metformin in Chinese people with newly diagnosed Type 2 diabetes

Abstract: Our findings suggest that rs2289669 might help predict the glycaemic response to metformin in Chinese people newly diagnosed with Type 2 diabetes, and that differential increases in basal glucagon-like peptide-1 concentration among rs2289669 genotypes might be associated with inter-individual response to metformin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Therefore, it seems that the increase seen in GLP-1 modulates the effect of metformin on glucagon secretion and consequently on EGP. It is important in this context to highlight that Liang, Xu [58] et al showed that adjustment for basal GLP-1 levels removed the statistical significance of the association between the rs2289669 of the SLC47A1 gene; encoding for the multidrug and toxin extrusion 1, a transporter involved in the hepatic and renal excretion of metformin, and enhanced glycemic response. Altogether these findings may implicate GLP-1 and glucagon in interindividual response variation to metformin.…”
Section: Could Hyperglucagonemia Underly An Adverse Response To Metfo...mentioning
confidence: 99%
“…Therefore, it seems that the increase seen in GLP-1 modulates the effect of metformin on glucagon secretion and consequently on EGP. It is important in this context to highlight that Liang, Xu [58] et al showed that adjustment for basal GLP-1 levels removed the statistical significance of the association between the rs2289669 of the SLC47A1 gene; encoding for the multidrug and toxin extrusion 1, a transporter involved in the hepatic and renal excretion of metformin, and enhanced glycemic response. Altogether these findings may implicate GLP-1 and glucagon in interindividual response variation to metformin.…”
Section: Could Hyperglucagonemia Underly An Adverse Response To Metfo...mentioning
confidence: 99%
“…Epidemiological evidence indicates that EOD exhibits a tendency of familial aggregation [12,13]. Recently, a large number of single nucleotide polymorphisms (SNPs) associated with the risk of T2DM have been discovered, but only a few studies have examined the infuence of such genetic heterogeneity on the age of onset of T2DM [14][15][16]. Te loss of insulin release, insulin resistance, and increased glucagon secretion also accelerate the development of T2DM.…”
Section: Introductionmentioning
confidence: 99%